Sample Surveys of Current Interest In India Nineteenth and Twentieth Annual Reports (1967-68 and 1968-69) - Planning Commission (Planning Commission, 1967)
The 22nd round of the National Sample Survey (NSS) was conducted from July, 1967 to June, 1968. It is a repetitive survey. 2. It was conducted on behalf of the Government of India. the Department of Statistics was responsible for over-all planning for the survey. the Indian Statistical Institute was responsible for the sampling design, schedules and instructions pertaining to the survey. The field work was the responsibility of the Directorate of National Sample Survey, Department of Statistics, Government of India except in West Bengal and Bombay City, where it was the responsibility of the Indian Statistical Institute (ISI). the object of the survey was to collect various types of socio-economic and crop data. The requirements of the data were submitted to the Central Statistical Organisation, Government of India, by the different Ministries, Government Departments and other interested Organisations.
Central Statistical Organisation Department of Statistics Cabinet Secretariat Government of India